Pengaruh Konseling Kelompok Teknik Restrukturisasi Kognitif Terhadap Kecemasan Karir Siswa Kelas XI SMK Madinatul Ulum - Yurike Kinanthy Karamoy; Marta Letisia; Fakhruddin Mutakin (UPT Publikasi dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2023)
This study aims to examine the effect of cognitive resolution technique group counseling on the career anxiety of class XI students at Madinatul Ulum Vocational School. This research is quasi-experimental. The respondents studied were 16 out of 60 students taken using a systematic sampling method. The data collection method used in this research is the questionnaire and documentary method. The instrument used in this research is a career anxiety scale questionnaire which contains 29 questions. Data analysis used the Wilxocon Signed Rank Test and the Mann Whitney Test with the help of the SPSS version 26 application. The results of this study stated that there was an influence of cognitive adjustment technique group counseling on the career anxiety of class XI students at Madinatul Ulum Vocational School. It was found that there was a difference in the average post-test score for career anxiety in the experimental group and the control group. It is recommended for future researchers to consider the individual factors of each respondent such as activeness, student seriousness, and consider every aspect of each indicator in order to obtain appropriate and optimal results._____________________________________________________________________Penelitian ini bertujuan untuk menguji pengaruh konseling kelompok teknik restrukturisasi kognitif terhadap kecemasan karir siswa kelas XI SMK Madinatul Ulum. Penelitian ini merupakan kuasi-eksperimental. Responden yang diteliti sebanyak 16 dari 60 siswa yang diambil dengan menggunakan metode sampling sistematis. Metode pengumpulan data yang digunakan dalam penelitian ini adalah metode angket dan dokumenter, instrumen yang digunakan dalam penelitian ini adalah angket skala kecemasan karir yang berisi 29 butir soal. Analisa data menggunakan Uji Wilxocon Signed Rank Test dan Uji Mann Whitney dengan bantuan aplikasi SPSS versi 26. Hasil penelitian ini menyatakan bahwa terdapat pengaruh konseling kelompok teknik restrukturisasi kognitif terhadap kecemasan karier siswa kelas XI SMK Madinatul Ulum. Ditemukan adanya perbedaan rata-rata nilai post-test kecemasan karir pada kelompok eksperimen dan kelompok kontrol. Direkomendasikan bagi peneliti selanjutnya untuk mempertimbangkan faktor individual dari masing-masing responden seperti faktor keaktifan, keseriusan siswa, dan mempertimbangkan setiap aspek dari masing-masing indikator agar mendapatkan hasil yang sesuai dan lebih maksimal lagi.